2012
DOI: 10.1371/journal.pone.0048670
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tankyrases Induces Axin Stabilization and Blocks Wnt Signalling in Breast Cancer Cells

Abstract: Constitutive Wnt signalling is characterized by excessive levels of β-catenin protein and is a frequent occurrence in cancer. APC and Axin are key components of the β-catenin destruction complex that acts to promote β-catenin degradation. The levels of Axin are in turn controlled by tankyrases, members of the PARP-family of poly-ADP-ribosylation enzymes. In colorectal cancer cells, which typically harbor APC mutations, inhibition of tankyrase activity promotes Axin stabilization and attenuates Wnt signalling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
103
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 55 publications
12
103
0
2
Order By: Relevance
“…An in vitro IC 50 test revealed that the IC 50 of XAV939 was 4 and 11 nM against activity of tankyrase-1 and tankyrase-2, respectively (15). Although XAV939 showed in vitro an IC 50 value with high selectivity, higher concentrations (5-10 M) of XAV939 were commonly chosen for cell-based experiments to examine the inhibitory effects of XAV939 on tankyrase activity and tankyrase-mediated Wnt signaling (1,8,14). Importantly, dDAVP-or forskolin-induced AQP2 upregulation was significantly attenuated by the inhibition of tankyrase with 10 M XAV939 treatment or siRNA-mediated knockdown, indicating that tankyrase and/or tankyrase-mediated signaling is importantly involved in AQP2 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro IC 50 test revealed that the IC 50 of XAV939 was 4 and 11 nM against activity of tankyrase-1 and tankyrase-2, respectively (15). Although XAV939 showed in vitro an IC 50 value with high selectivity, higher concentrations (5-10 M) of XAV939 were commonly chosen for cell-based experiments to examine the inhibitory effects of XAV939 on tankyrase activity and tankyrase-mediated Wnt signaling (1,8,14). Importantly, dDAVP-or forskolin-induced AQP2 upregulation was significantly attenuated by the inhibition of tankyrase with 10 M XAV939 treatment or siRNA-mediated knockdown, indicating that tankyrase and/or tankyrase-mediated signaling is importantly involved in AQP2 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…cer, hepatocarcinoma, medulloblastoma, ovarian cancer, and breast cancer) can also exhibit loss of functional axin or other mutations that stabilize ␤-catenin expression (21)(22)(23)(24)(25)(26). These findings have prompted researchers to develop inhibitors of the WNT/ ␤-catenin signaling pathway for therapeutic use to treat cancer, although the vast majority of these are still at the preclinical testing stage (27).…”
Section: Figmentioning
confidence: 99%
“…However, inhibition of TNKS is not sufficient to fully suppress Wnt signaling, resulting in only partial tumor growth inhibition (15). Several reports have also shown that the antitumor effect following TNKS inhibition is more robust under serumdeprived conditions (8,15,20,21), raising the possibility that TNKS inhibition may be more effective when combined with other therapies. This idea is supported by two studies reporting that TNKS inhibition could alleviate resistance to EGFR inhibitors in non-small lung cancer cell lines and potentiates colorectal cancer cell response to PI3K/AKT pathway inhibitors (22,23).…”
Section: Introductionmentioning
confidence: 99%